Mineralization, Biodegradation, and Antagonistic Activities of Gut-associated Bacteria and Fungi of African Nightcrawler, Eudrilus eugeniae (Kinberg, 1867) - Mapile, Maria Reynalen F.; Obusan, Marie Christine M. (Science Diliman: A Journal of Pure and Applied Sciences; Vol 32 No 1 (2020), 2020)
Earthworms and their interactions with microorganisms offer beneficial effects that can improve organic matter decomposition, enhance nutrient availability, and suppress pathogens in the soil. In this study, microorganisms from the gut of Eudrilus eugeniae (Kinberg, 1867), commonly known as African nightcrawler or ANC, were isolated through pour plate method and screened for their activities using assays to confirm nitrogen fixation, phosphate solubilization, polyethyleneutilization, and antagonistic potential. The identifications of eight bacterial and six fungal isolates were confirmed based on nearest phylogenetic affiliations. Fungal isolates Aspergillus aculeatus , Aspergillus japonicus , Fomitopsis sp., and Penicillium citrinum exhibited antagonistic activity against Bacillus subtilis ,  Escherichia coli , Pseudomonas aeruginosa , and Staphylococcus aureus . Bacterial isolates Aeromonas caviae and Bacillus xiamenensis utilized low- and high-density polyethylene as carbon sources. These isolates were also found to have high phosphate solubilization index (2.55-2.67) with high amount of phosphate solubilized ( A. caviae : 0.799; B. xiamenensis : 0.778) at decreasing pH (i.e. pH 7.0 to 4.0). A. caviae and B. xiamenensis also showed nitrogen-fixing activity which is supported by the detection of nifH gene (>300 bp) and high nitrogen content (50 kg/ha NO3-N) of vermicasts. The activities of these gut-associated bacteria and fungi must be further explored to optimize the use of ANC’s casts and compost for agricultural, medical, and other applications.
Keywords: antagonistic activity, earthworm, microorganisms, nitrogen fixation,phosphate solubilization, polyethylene utilization